The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/srin.202200674
|View full text |Cite|
|
Sign up to set email alerts
|

Nucleation, Growth, Sintering, and Densification of Sulfide in 1215MS Free‐Cutting Steel Billet

Abstract: Herein, the nucleation, growth, aggregation, sintering, and densification of sulfide in 1215MS free-cutting steel billet with a total oxygen concentration of 70 ppm are investigated. A portion of oxygen in the steel dissolves in sulfide to form oxysulfide, Mn(S,O), which can be single-particle spherelike (SPS), doubleparticle rodlike (DPR), and multi-particle rodlike (MPR), and SiO 2 can precipitate at the outer edge of the SPS and connection in the DPR and MPR inclusion particles to form Mn(S,O)-SiO 2 inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Simultaneously, confirming the promoting effect of alloy elements on the growth of MnS, which is consistent with the results reported in previous publication. [ 34 ] In contrast, through the values of increase in element concentration and the corresponding decrease in solid phase fraction, it can be found that C element is more effective in promoting the precipitation of MnS, followed by Si and Mn elements. This phenomenon may be attributed to the high sensitivity of C element on changes in the liquid‐solid phase zone, which affects the distribution coefficient of solutes during solidification, leading to early precipitation of MnS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, confirming the promoting effect of alloy elements on the growth of MnS, which is consistent with the results reported in previous publication. [ 34 ] In contrast, through the values of increase in element concentration and the corresponding decrease in solid phase fraction, it can be found that C element is more effective in promoting the precipitation of MnS, followed by Si and Mn elements. This phenomenon may be attributed to the high sensitivity of C element on changes in the liquid‐solid phase zone, which affects the distribution coefficient of solutes during solidification, leading to early precipitation of MnS.…”
Section: Resultsmentioning
confidence: 99%
“…From the above analysis results, it found that the manganese‐containing inclusions in MMC10, MHC10, and MS10 steel are mainly large irregular MnS inclusions, which can be considered that Type III of MnS is caused by boosting divorced eutectic transformation under the action of C and Si elements. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese Sulphide (MnS) inclusions were observed in the steel through optical microscopy as finely dispersed particles with globular morphology, as presented in Figure 4. These inclusions are classified as type I and are formed when oxygen and sulfur solubilities are high and low, respectively [37][38][39][40].…”
Section: Inclusions Observationmentioning
confidence: 99%